CHALLENGES IN RECORDING AND REPORTING ASSETS - Rahayu, Rika; Arsal, Muryani; Nurhayati; Usman (PT. Jurnal Center Indonesia Publisher, 2025)
MSMEs (Micro, Small and Medium Enterprises) play a very important role in the Indonesian economy, especially in creating jobs and empowering communities. However, MSMEs often face significant challenges in recording and reporting their financial assets. This study aims to identify the main challenges faced by MSMEs in recording and reporting assets, analyze the factors that cause a lack of accuracy in asset recording, and evaluate the effect of limited managerial knowledge and access to technology on the quality of financial reports. The research method used is a qualitative approach with in-depth interviews with MSME owners/managers and field observations. The results of the study indicate that lack of accounting knowledge, limited human resources, and minimal technological support are the main factors that hinder accurate asset recording. In addition, inaccuracies in financial reports can have a negative impact on the ability of MSMEs to obtain funding from financial institutions or investors. Therefore, efforts are needed to increase capacity through management training and the use of accounting technology to improve the transparency and accuracy of MSME financial reports.